Development of a Habit Learning Model; Habitation and Positive Reinforcement Strategy for Pe Subjects to Improve Physical Activity in High School Students - Saitya, Imaduddin; Muhadi, Muhadi; Adawiyah, N. R. (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to develop a habit-learning-based physical education (PJOK) learning model with habituation strategies and positive reinforcement to form sustainable physical activity habits in high school students. The method used is research and development (R&D) with the Borg & Gall model. The subjects of the study were grade X IPS I students of SMAN 1 Langgudu, Bima Regency. The research instruments were questionnaires and interviews to measure student motivation and responses after the model was implemented. The results of a limited trial showed that the implementation of the habit learning model obtained an average response of 62.70% in the good category. A total of 78.9% of students rated this model as good, while 21.1% rated it as sufficient, with no ratings being very good or poor. These findings indicate that the developed learning model is practically feasible, although it still requires improvements in the aspects of rewards, consistency of habituation, and optimization of digital media to increase its effectiveness. Thus, the habit learning model has the potential to support the goal of physical education in forming a lifelong healthy lifestyle.